IS THE ROLE OF FATHER’S PARENTING IMPORTANT FOR THE CHARACTER BUILDING OF STUDENTS? - Wulan Sari Putri Hidayat; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
The strength of character can be manifested through the interactions of parents, especially fathers, in the parenting process. This study aimed to analyze the influence of student characteristics, family characteristics, and the role of fathers' parenting on character strength. This study used an explanatory design involving 289 first-year students living with complete parents. Sampling was taken by voluntary sampling. Data were obtained by self-reporting through online questionnaires and analyzed by multiple linear regression using SPSS. The findings show that there are nine indicators of paternal parenting such as positive involvement, positive emotional response, negative involvement, moral roles, gender roles, provider roles, androgynous roles, father's presence, and father's responsibility. In addition, there are three indicators of the strength of characters, such as moral knowledge, moral feelings, and moral action, which contain six virtues in the form of wisdom, justice, humanity, determination, self-control, and spirituality. The study's results prove that the role of a father's parenting significantly positively affects character strength. Overall, the strength of student character cannot be separated from the role of family care, especially for fathers.